Correspondence between grey-body factors and quasinormal frequencies for rotating black holes - R.A. Konoplya; A. Zhidenko (Physics Letters B)
Although the proper oscillation frequencies of black holes (quasinormal modes) and the grey-body factors, which determine the scattering properties of black holes, represent two distinct spectral problems with different boundary conditions, a recent study has revealed an intrinsic connection between these quantities. We have shown that the correspondence between grey-body factors and quasinormal modes, previously established for spherically symmetric and asymptotically flat black holes, also extends to general parametrized axially symmetric black holes. This correspondence is limited to non-superradiant waves.